Contextual and psychosocial factors associated with latrine utilization in rural communities in Ethiopia - Bamlaku Golla, Eyasu; Geremew, Habtamu; Abate, Alegntaw; Ahmed Ali, Mohammed; Simegn, Mulat Belay; Wondie, Smegnew Gichew; Kumbi, Hawi; Kuse, Samuel Abdisa (Frontiers in Public Health, 2024)
BackgroundAlthough proper latrine utilization is one of the best ways to reduce the risk of infection, it remains a challenge in the majority of rural communities in developing countries such as Ethiopia. Studies have demonstrated the link between individual behavior and latrine use, but there is a paucity of evidence on individual risk perception, perceived social pressure norms, social identity, and perceived ability, which plays an indubitable role in health and behavior change, especially in rural communities.ObjectiveThis study aimed to identify contextual and psychosocial factors associated with latrine utilization among rural communities in Lomabosa district, Ethiopia.MethodsA rural community-based cross-sectional study was conducted in June 2022 among rural households (HHs) in Lomabosa district, Ethiopia. A systematic random sampling method was used to select participant households. Data were collected using a pretested structured questionnaire via face-to-face interviews and on-the-spot observations. Stata version 14.1 software was used for statistical analysis. A binary logistic regression model was used to run the bivariable and multivariable analysis of the data. Variables with p < 0.25 at bivariable logistic regression analysis were entered into the multivariable analysis. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to show the strength of the association, and the statistical significance was declared at p < 0.05.ResultsOf the 682 computed sample sizes, 665 households participated in this study with a response rate of 97%. Accordingly, our analysis found that 67% (95% CI, 63.7–70.5) of households utilize their latrine properly. Educational status (AOR = 2.01; 95% CI: 1.01–2.08), wealth index (AOR = 2.3; 95% CI: 1.23–3.58), perceived susceptibility (AOR 3.2; 95% CI: 1.26–5.14), injunctive norm (AOR 1.9; 95% CI: 1.13–3.18), and perceived ability (AOR 1.9; 95% CI: 1.04–3.79) were identified as contextual and psychosocial factors associated with latrine utilization.Conclusion and recommendationsThis study found that educational status, wealth index, perceived susceptibility, injunctive norm, and perceived ability were the contextual and psychosocial factors associated with latrine utilization. Therefore, information intervention for the low perception of health risk, persuasive and normative interventions for changing norm factors, and infrastructural and other ability support for ability factors should be addressed.